Development of ovarian tumour causes significant loss of muscle and adipose tissue: a novel mouse model for cancer cachexia study. Issue 2 (19th January 2022) - Luan, Yi; Zhang, Yaqi; Yu, Seok‐Yeong; You, Mikyoung; Xu, Pauline C.; Chung, Soonkyu; Kurita, Takeshi; Zhu, Jie; Kim, So‐Youn
Abstract: Background: Cancer‐associated cachexia (CAC) is a complex syndrome of progressive muscle wasting and adipose loss with metabolic dysfunction, severely increasing the morbidity and mortality risk in cancer patients. However, there are limited studies focused on the underlying mechanisms of the progression of CAC due to the complexity of this syndrome and the lack of preclinical models that mimics its stagewise progression. Methods: We characterized the initiation and progression of CAC in transgenic female mice with ovarian tumours. We measured proposed CAC biomarkers (activin A, GDF15, IL‐6, IL‐1β, and TNF‐α) in sera ( n  = 6) of this mouse model. The changes of activin A and GDF15 ( n  = 6) were correlated with the decline of bodyweight over time. Morphometry and signalling markers of muscle atrophy ( n  ≥ 6) and adipose tissue wasting ( n  ≥ 7) were assessed during CAC progression. Results: Cancer‐associated cachexia symptoms of the transgenic mice model used in this study mimic the progression of CAC seen in humans, including drastic body weight loss, skeletal muscle atrophy, and adipose tissue wasting. Serum levels of two cachexia biomarkers, activin A and GDF15, increased significantly during cachexia progression (76‐folds and 10‐folds, respectively). Overactivation of proteolytic activity was detected in skeletal muscle through up‐regulating muscle‐specific E3 ligases Atrogin‐1 and Murf‐1 (16‐folds and 14‐folds, respectively) with decreasing cross‐sectional area of muscle fibres ( P  < 0.001). Muscle wasting mechanisms related with p‐p38 MAPK, FOXO3, and p‐AMPKα were highly activated in concurrence with an elevation in serum activin A. Dramatic fat loss was also observed in this mouse model with decreased fat mass ( n  ≥ 6) and white adipocytes sizes ( n  = 6) ( P  < 0.0001). The adipose tissue wasting was based on thermogenesis, supported by the up‐regulation of uncoupling protein 1 (UCP1). Fibrosis in adipose tissue was also observed in concurrence with adipose tissue loss ( n  ≥ 13) ( p  < 0.0001). Conclusions: Our novel preclinical CAC mouse model mimics human CAC phenotypes and serum biomarkers. The mouse model in this study showed proteolysis in muscle atrophy, browning in adipose tissue wasting, elevation of serum activin A and GDF15, and atrophy of pancreas and liver. This mouse line would be the best preclinical model to aid in clarifying molecular mediators of CAC and dissecting metabolic dysfunction and tissue atrophy during the progression of CAC.